Keterhubungan Emosional Sebagai Strategi Autentisitas Dalam Persona Digital Model di Media Sosial - Aileen kurniawan; Christian Anggrianto (Serat Rupa: Journal of Design, 2026)
The self-image of a digital worker—particularly a model—is largely shaped through social media, which serves as an interactive medium between the figure and the audience (Iswanto et al., 2020). The distinguishing factor among models lies in their personal branding, however, social media algorithms tend to favor trending content. This results in micro/nano models struggling to form a strong personal brand, either showcasing their distinctive traits, or follow mainstream trends but losing their authenticity. This study aims to explore effective strategies and solutions for models to develop their personal branding through aesthetic curation, tone of communication, parasocial relationships, and trend adaptation without compromising their identity. Using a descriptive qualitative approach, data were collected from journal analyses, as well as surveys involving 30 creative industry professionals and 33 active social media users. The results show that 63.3% of industry professionals prefer models who also act as content creators and demonstrate high engagement to strengthen brand objectives. From the audience’s perspective, 63.3% respondents that content that showcases personality and daily life are more appealing, as they seek to apply what they see on social media as inspiration in their own lives. Thus, both journal findings and survey results indicate that models who combine visually curated aesthetics with a humanized portrayal of their personality and life tend to be more engaging and in demand.